Spillover effects of Germany's final demand on Southern Europe - Enno Schröder; Oliver Picek (Institut für Makroökonomie und Konjunkturforschung (IMK), Hans-Böckler-Stiftung, 2017)
We calibrate a closed multi-country input-output model with data from the World Input-Output Database to estimate the size of spillover effects of Germany's final demand on GDP, employment, and the trade balance in Southern European countries. We find that spillover effects are rather small. Germany alone will hardly make a significant contribution to the external adjustment process in the European South.
Keywords: F14; F32; F42; C67; 330; euro area; macroeconomic imbalances; external adjustment; input-output analysis; global value chains; spillover effects